Changing Ecosystems and Their Services - Hufnagel, Levente (IntechOpen, 2020)
Changing Ecosystems and their Services provides a very interesting account of the frontiers of biodiversity and ecological research. It consists of seven chapters covering mass extinctions: the "Big Five" and "The Sixth", which are recent global ecological crises, Caribbean biodiversity, acoustic habitat degradation due to shipping in the world's oceans, methane production of microbes in Amazonian floodplains, African mangrove forests, pollination as ecosystem services in Ethiopia, and climate change management. I am sure that this book will be very useful for everybody-researchers, teachers, students, or others interested in the field-who would benefit from insight into biodiversity research.